Biologia reprodutiva de espécies de Chamaecrista Moench. (Fabaceae – Caesalpinioideae) em uma área de restinga de Pernambuco - ALMEIDA, Natan Messias de (2011)
Enantiostyly is a floral polymorphism that includes reciprocal hercogamy, resulting in flowers that form mirror images. One floral morph present sexual elements positioned at the right side of the flower and the other morph present these elements turned to the left. This mechanism is interpreted as a strategy that maximizes cross pollination. Many species of the genus Chamaecrista have been recorded as monomorphic enantiostylous, then, present two floral morphs in the same individual. Considering that the genus is very common in restinga vegetation, that is an extremely altered ecosystem, and the lack of knowledge in relation to several aspects of enantiostyly, the aim of this study is to investigate the reproductive biology of two Chamaecrista species in an area of restinga vegetation of Pernambuco state, Brazil, focusing aspects of enantiostyly. The first chapter includes the investigation of the functioning of enantiostyly in C. ramosa through data on floral biology, floral visitors’ behavior, breeding system and other aspects related to the reproductive biology. This species presented patterns of pollen deposition and capture that are typical of enantiostylous species described by other studies. It is self-compatible, being visited exclusively by bees. The second chapter reports the enantiostyly in C. flexuosa, including morphological, morphometric and reproductive aspects. Taking into account only the floral morphology, the species presents two floral morphs (left and right), but when the functioning of the enantiostyly was checked, a third floral morph was recognized (central). Considering the results obtained here, it is possible to conclude that the enantiostyly presents different functions in the two species, suggesting the possibility of deviations of the classical pattern of enantiostyly.